The Diachronic Mind - Slors, M.V. author. aut Link
VIII, 238 p.
Keywords: vii 1 ~OOUCTIONANOOVERVlliW 1 2 SEITING THE STAGE: PERSONAL IDENTITY ANO THE MErAPHYSICS OFMIND 1. Introduction 6 2. The Problem of Personal Identity over Time 7 3. The Psychological Criterion of Personal Identity over Time 12 4. The Neo-Lockean Psychological Criterion of Personal Identity 16 5. The Circularity Objection 19 6. Problems of Logical Form 21 7. The Lack of a Third-Person Criterion for Reidentification 23 8. The Unity of the Mental Bundle 25 9. The Individuation ofPersons 26 10. The Neo-Lockean Criterion and Physicalism: a 'Natural' Alliance 28 11. One 'Solution' to Five Problems 35 3 PARFIT'S REDUcrIO OF A SUBSTRATUM-ORIENTEO CONCEPfION OF PSYCHOLOGICAL CONTINUlTY 43 1. Introduction 2. Relation R 45 51 3. Relation R and the Neo-Lockian Paradigm 4. Psychological Atomism 56 61 5. The Central Place of Q-Memory in the Neo-Lockean Paradigm 64 6. The Trouble with Q-memory 74 7. Contents and Contexts. The Other Four Problems 79 8. Conclusions 4 A CON1ENT-ORIENTEO CONCEPTION OF PSYCHOLOGICAL CONTINUITY 82 1. Introduction 83 2. Two Kinds of Psychological Continuity 91 3. Levels of N-Continuity 93 4. The Unity of N-Continuous Sequences. The Role of the Body 105 5. N-Continuity and Psychological Connectedness 109 6. Summary vi 5 A PSYCHOLOGICAL CRI1ERION OF PERSONAL IDENTITY: THE AVE PROBLEMS REVISITED 1. Introduction 111 2. Circularity, Q-Memory, and N-Continuity 112 119 3. Narrativity and Logical Form 127 4. Third-Person Criteria of Reidentification: The Role of the Body 5.